RFID and ERP systems in supply chain management - Pejvak Oghazi; Fakhreddin Fakhrai Rad; Stefan Karlsson; Darek Haftor (European Journal of Management and Business Economics (EJM&BE), 2018)
Purpose: The purpose of this paper is to identify the impact of enterprise systems (ESs), in particular radio frequency identification (RFID) and enterprise resource planning (ERP) systems, on supply chain management (SCM). The results of this conceptual paper demonstrate that ERP and RFID systems contribute to SCM by improving supply chain integration. Supply chain integration occurs to facilitate the flow of financing, products, and information throughout the chain. In this regard, ERP and RFID contribute to integration by enhancing the information flow across the supply chain. Design/methodology/approach: This paper proposes a conceptual model developed from the findings of literature review within the research domains of SCM, ESs, and supply chain integration. Findings: This conceptual study contributes to the existing theory by linking the concept of information technology, ESs to SCM. The conceptual model in this paper may provide insights for executives who wish to implement ERP or RFID systems in their businesses in order to achieve higher integration, both within internal sectors and also with supply chain partners. Originality/value: The findings in this study contribute to the theory base by linking the concept of information technologies, ESs to SCM. The conceptual model presented in this paper can provide insights for executives who wish to implement ERP or RFID systems in their businesses in order to achieve higher integration within internal sectors and with supply chain partners. This study offers new understandings by investigating the impact of ERP and RFID together on SCM.
Keywords: 650; Enterprise resource planning (ERP); Supply chain management; Information technology; Supply chain integration; Enterprise systems; Radio frequency identification (RFID)